Thermomechanical advantages of functionally graded dental posts: A finite element analysis. Issue 8 (18th April 2019) - Dabbagh, Ali; Madfa, Ahmed; Naderi, Sadjad; Talaeizadeh, Mahtab; Abdullah, Hadijah; Abdulmunem, Mohamed; Kasim, NH Abu
ABSTRACT: This study aimed to fabricate dental posts with functionally graded structures comprised of zirconia, titanium, and hydroxyapatite and compare their thermomechanical behavior with homogeneous zirconia and titanium posts in simulated models of upper central incisor. The results indicated the gradual behavior of functionally graded dental posts in terms of physical and mechanical properties. The finite element analysis revealed a more efficient equilibration to the oral environment after removing the thermal stress in functionally graded dental post compared to the homogeneous counterparts. Therefore, the functionally graded structures could reduce the stress/strain concentrations and interfacial stresses in root canal and minimize the likelihood of root fracture.